ANALISIS PERMASALAHAN SIKAP PROFESIONALISME DALAM KINERJA GURU PADA SATUAN PENDIDIKAN - Fani Susanti; Afan Alfian Rizal; Dwi Erni Febrianti (BASA Journal of Language & Literature, 2021)
This paper aims to find out the problem of professionalism in teacher performance in the education unit. This writing uses a descriptive qualitative approach in which to find relevant and valid reading sources to collect accurate data in an effort to support this writing. Basically the problem with professional attitudes arises a lot because of the number of teachers who only master knowledge but do not master some other aspects. So it only teaches but ignores the most important value in education itself. These problems arise due to a lack of self-awareness in an educator. Professionalism is an aspect of expertise in the field that is run. So that efforts to develop, improve, and self-evaluation in educators must be pursued and must be continuously improved. Considering educators are a central and key aspect in achieving educational goals. Teachers with good performance will produce human resources and outputs that will be very beneficial to the nation and the country. Some of the problems in this case are about professionalism towards legislation, professionalism towards peers, profeionalism attitude towards learners, and professionalism attitude towards superiors or leaders. That will be analyzed in this paper to find out the magnitude or small impact that resulted from this.